Beyond profit: maqasid al-Shari’ah in Islamic finance through partnership contracts (ʿUqud al-Ishtirak) - As-Salafiyah, Aisyah; Ali, Mohammad Mahbubi; Rusydiana, Aam Slamet (Springer, 2025)
Islamic finance has undergone remarkable growth over the past four decades, establishing itself as a significant sector in the global financial landscape. Rooted in Shariah principles, Islamic finance promotes justice, fairness, and public welfare through distinct mechanisms such as profit- and loss-sharing while prohibiting unethical practices like usury (riba), uncertainty (gharar), and gambling (maysir). Partnership contracts (ʿUqūd al-Ishtirāk), particularly mushārakah and muḍārabah, exemplify these principles by fostering equitable wealth distribution, cooperation, and sustainable economic development. This study explores the Shariah objectives (maqāṣid al-Sharīʿah) underpinning mushārakah and muḍārabah contracts within Islamic finance. Employing a qualitative approach, it integrates primary sources such as classical jurisprudence texts and secondary sources including academic literature. The analysis highlights the principles of risk-sharing, fairness, and justice embedded in these contracts, with a focus on their practical implementation and alignment with maqāṣid al-Sharīʿah. The paper also examines Malaysia’s pioneering efforts in promoting partnership contracts, showcasing its leadership in aligning regulatory frameworks with Shariah principles. Insights from this study are expected to guide policymakers and financial institutions in leveraging mushārakah and muḍārabah to foster inclusive, entrepreneur-friendly, and socio-economically sustainable environments. By emphasizing the maqāṣid al-Sharīʿah in partnership contracts, this research underscores their potential to contribute to a more equitable and just economic system, positioning Islamic finance as a key driver of sustainable development globally.